Celiac Disease Presenting with Vitamin D Deficiency and Low Bone Mineral Density in the Puerperium - Mustafa ÜNÜBOL; Engin GÜNEY; Volkan YAZAK; Umut ÇAKIROĞLU; Adil COŞKUN; İbrahim METEOĞLU4 (Archives of Rheumatology, 2012)
Celiac disease (CD) is an autoimmune disease triggered by the ingestion of foods containing gluten (gliadin). Celiac disease is usually diagnosed in childhood. Celiac disease, which has an insidious onset in adults, is rarely seen in the puerperium. A 26-year-old female admitted with the complaints of cramps in her hands and feet, and weight loss in the puerperium. Vitamin D deficiency was found with concomitant hypocalcemia and low bone mineral density. The patient was diagnosed with CD in the puerperium by means of biopsy and antibody testing. From the first week of the gluten-free diet and supportive therapy, remarkable improvement was observed in the patient’s clinical manifestations. In conclusion, although CD is a disease frequently diagnosed during childhood, it should not be overlooked for the maternofetal health that CD may also develop during pregnancy and the puerperium.